(untitled) (Raparin Journal of Humanities (RJH), 2023)
This academic paper investigates whether accounting fraud has been detected with the use of computerized accounting information systems (CAIS) and what can be done to protect a company’s fear resources from theft or misuse. Even though organizations in the current era are confronted with technological advancements, but still no previous study in the construction sector has investigated these subject matters through the lens of CAIS. To obtain the objectives of the study, self-administrated questionnaires were designed on a five-point Likert scale to collect data, judgment sampling was applied, and the sample size was 140. Independent variables of the study represent features of CAIS, while dependent variables represent detecting fraud. Empirically the statistical SPSS software has been used to analyse the identified data and concluded results indicate features of CAIS through internal control, audit procedures and good governance as construct moderating variables enable organizations to detect fraud.